2010
DOI: 10.2967/jnumed.109.070094
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Measurement of Vesicular Monoamine Transporter Type 2 Density in Parkinson Disease with 18F-AV-133

Abstract: PET provides a noninvasive means to evaluate the functional integrity of the presynaptic monoaminergic system in the living human brain. Methods: In this study, a novel 18 F-labeled tetrabenazine derivative, 18 F-(1)fluoropropyldihydrotetrabenazine ( 18 F-AV-133), was used for the noninvasive assessment of the vesicular monoamine transporters type 2 (VMAT2) in 17 Parkinson disease (PD) patients and 6 healthy controls. The binding potential (BP) of 18 F-AV-133 was calculated using Logan graphical analysis. Voxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
85
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 27 publications
(53 reference statements)
15
85
0
Order By: Relevance
“…. This is consistent with previous studies on PD patients [23] . On day 15, no significant correlation was found between the subscores for rigidity …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…. This is consistent with previous studies on PD patients [23] . On day 15, no significant correlation was found between the subscores for rigidity …”
Section: Discussionsupporting
confidence: 94%
“…2). After 15 days of MPTP exposure, the SUrs of right and left side striatum of PD patients, next in the anterior putamen (−70%), and then in the caudate nucleus (−48%) [23] , which is consistent with our results. In 2010, [ 11 C]DTBZ PET imaging was used to evaluate the model of chronic MPTP-induced parkinsonism in monkeys induced by a low dose of MPTP administered over several months [33] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These brain regions have been recognized as being related to dopamine-(nigrostriatal pathway) and serotonin (hippocampus and brain stem)-secreting neurons (35). A recent publication demonstrated the ability to differentiate healthy controls from PD subjects using 18 F-AV-133 targeting VMAT2 (20). In addition, because uptake of 18 F-AV-133 in the brain was not restricted to the nigrostriatal system, possible applications for studying the serotonin system relating to psychiatric disorders is also warranted.…”
Section: Discussionmentioning
confidence: 99%
“…An initial trial to assess the reduction of VMAT2 binding sites in patients with PD and dementia with Lewy bodies was performed by Koeppe et al (18) and Suzuki et al (19). A recent publication clearly indicated the sensitivity of 18 F-AV-133 for detecting monoaminergic terminal reductions in PD patients and concluded that 18 F-AV-133 may allow the selection of presymptomatic patients with nigrostriatal movement disorders (20).…”
mentioning
confidence: 99%